Intention to Use Voluntary Disclosure Information on Social Media for Investment Decisions: Analysis Using Perceived Ease of Use and Perceived Usefulness - Gunawan Wibisono; Soon Yong Ang (Universitas Pasundan, 2019)
This study analyzes investor behavior when using voluntary disclosure information posted on social media pages in their investment decision-making. To measure the relationship between belief constructs and behavioral intention, the technology acceptance model was used. To this end, two belief constructs were employed: 1) perceived ease of use and 2) perceived usefulness. These constructs were applied to the intention to use voluntary disclosure information posted on social media pages in the investment decision-making process. The study examined 150 employees as respondents, using structural equation modeling for hypothesis testing. The findings showed that investors in Indonesia viewed voluntary disclosure information posted on social media pages as affecting their intention to use such information in the process of investment decision-making. Both perceived ease of use and perceived usefulness affected the aforementioned intention. The study also found that perceived ease of use had both a direct and an indirect effect through perceived usefulness.